2020
DOI: 10.1002/macp.202000254
|View full text |Cite
|
Sign up to set email alerts
|

Dot Nanopattern Self‐Assembled from Rod‐Coil Block Copolymer on Substrate

Abstract: Nanoscale dot patterns are important in various fields. However, it is still a challenge to fabricate ordered nanopatterns on substrates through a polymer self‐assembly approach. In this work, it is reported that polypeptide‐based rod‐coil block copolymers can self‐assemble into surface micelles on substrates, thus forming dot nanopatterns. The size of the surface micelles is readily adjusted by the degree of the polymerization of the block copolymers. It is found that most of the surface micelles are in a six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In that system, the BCPs first form small aggregates in solution, then some aggregates anchor to the substrate, which serves as the seeds to trigger living growth of elongated micelles by incorporating the remaining small aggregates in the solution. We also found that through an adsorption‐assembly process of polypeptide BCPs can form ordered surface nanostructures on substrates, including well‐aligned stripe nanopatterns on plain substrates and orderly arrayed dot nanopatterns on microspheres formed by PBLG‐ b ‐PEG BCPs 60–65 . For example, Tang et al prepared micrometer‐scale and well‐aligned polypeptide stripe nanopatterns on a plain substrate 60 .…”
Section: Novel Self‐assembly Methods For Polypeptidesmentioning
confidence: 76%
See 1 more Smart Citation
“…In that system, the BCPs first form small aggregates in solution, then some aggregates anchor to the substrate, which serves as the seeds to trigger living growth of elongated micelles by incorporating the remaining small aggregates in the solution. We also found that through an adsorption‐assembly process of polypeptide BCPs can form ordered surface nanostructures on substrates, including well‐aligned stripe nanopatterns on plain substrates and orderly arrayed dot nanopatterns on microspheres formed by PBLG‐ b ‐PEG BCPs 60–65 . For example, Tang et al prepared micrometer‐scale and well‐aligned polypeptide stripe nanopatterns on a plain substrate 60 .…”
Section: Novel Self‐assembly Methods For Polypeptidesmentioning
confidence: 76%
“…We also found that through an adsorption-assembly process of polypeptide BCPs can form ordered surface nanostructures on substrates, including well-aligned stripe nanopatterns on plain substrates and orderly arrayed dot nanopatterns on microspheres formed by PBLG-b-PEG BCPs. [60][61][62][63][64][65] For example, Tang et al prepared micrometer-scale and well-aligned polypeptide stripe nanopatterns on a plain substrate. 60 With the addition of water to the solution of PBLG-b-PEG BCPs containing a PS-modified Si substrate, the BCPs are adsorbed and assembled on the substrate into well-aligned nanostrips.…”
Section: Substrate-mediated Polypeptide Self-assembly Toward Ordered ...mentioning
confidence: 99%
“… 47 In such a packing manner, the shell of the spirals occupied by PEG 112 blocks is about 16 nm, which accounts for a reasonable PEG stretching degree of 41% (the full stretched length of PEG 112 is about 39 nm). 48 , 49 In addition, considering that the diameter of the PBLG is about 1.4 nm, 22 we can infer that there could be about 4–5 layers of PBLG chains in the spiral strands.…”
Section: Resultsmentioning
confidence: 99%
“…The periodicities of distinctive scales from side chain LC ordering and main-chain segregation of the counter-blocks will be co-existed and hence the hierarchical self-assembly will be governed by the combination of different driving forces [19]. Accordingly, modified models based on the SCFT approach [20] or dissipative particle dynamics (DPD) simulations [21][22][23] were developed to characterize the self-assembly behavior in SCLC or rod-coil BCP. Based on the experimental and theoretic studies, the hierarchical self-assembly system exhibits morphologies significantly different from those derived from conventional amorphous BCPs based on coil-coil model.…”
Section: Introductionmentioning
confidence: 99%